900+900+3x=700+500+9x

Simple and best practice solution for 900+900+3x=700+500+9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 900+900+3x=700+500+9x equation:


Simplifying
900 + 900 + 3x = 700 + 500 + 9x

Combine like terms: 900 + 900 = 1800
1800 + 3x = 700 + 500 + 9x

Combine like terms: 700 + 500 = 1200
1800 + 3x = 1200 + 9x

Solving
1800 + 3x = 1200 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
1800 + 3x + -9x = 1200 + 9x + -9x

Combine like terms: 3x + -9x = -6x
1800 + -6x = 1200 + 9x + -9x

Combine like terms: 9x + -9x = 0
1800 + -6x = 1200 + 0
1800 + -6x = 1200

Add '-1800' to each side of the equation.
1800 + -1800 + -6x = 1200 + -1800

Combine like terms: 1800 + -1800 = 0
0 + -6x = 1200 + -1800
-6x = 1200 + -1800

Combine like terms: 1200 + -1800 = -600
-6x = -600

Divide each side by '-6'.
x = 100

Simplifying
x = 100

See similar equations:

| 1/2I+9=14 | | 3x-3(4x-17)=96 | | 8y/12=6/9 | | 5x-11=35 | | 3*(3/4)^2-2*3/4 | | 4(c+6)=1/2(-2c-20) | | -4x+3(3x-17)=-76 | | 4b-4-11b-6= | | c-2/2+12=36 | | 0=0.001(0.732x^2+15.417x+605.738) | | 900+900+3x=700+500+9z | | x+1=7x | | 5x+12=4x+8 | | 49-49+81= | | 5x-2(6x+12)=53 | | 6x-3(6x-10)=162 | | x+10/2=42 | | 2x-2(2x-3)=-6 | | 2(x+4)=5xw+1 | | -3+-3+-2+-2+-2+-2+-1+-1+0+0+1+1+3+4= | | 4=(2+x)/2 | | 10j-10=3j-5 | | 7(x-3)=-4 | | -1=(8+x)/2 | | -4y+8=-2(4y+8) | | 7x+-1=4x+3 | | 0.4x+0.2(30)=0.3(x+30) | | -5x-7(-3x+9)=113 | | 9(z-3)=2(z+1) | | 4x+23=12x-76 | | 3y^2-3y-22=0 | | 5t-t-7=3t-5 |

Equations solver categories